2006
DOI: 10.1177/153331750602100111
|View full text |Cite
|
Sign up to set email alerts
|

The corpus callosum in Pick's disease, Alzheimer's disease, and amyotrophic lateral sclerosis: Gliosis implies possible clinical consequence

Abstract: Lesions of the corpus callosum have the potential to interfere with a neurologically impaired individual's ability to function in day-to-day activities, since the corpus callosum is important for a number of higher-order activities that involve information transfer between the left and right hemispheres. Even in normal individuals, callosal lesions may lead to apraxia, agraphia, and even an alien hand syndrome whereby the person is unable to control the actions of a hand. It is easy to envisage that callosal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
(22 reference statements)
1
10
0
Order By: Relevance
“…We next addressed the question whether HSPB8 and BAG3 expression may be upregulated in brain under neuropathological conditions characterized by the accumulation of misfolded aggregate‐prone proteins, including AD, PD, HD and SCA3 (Table S2). Under all these four pathological conditions, neurodegeneration is usually also accompanied by astrogliosis and microglia activation in the degenerating areas [2,42–45]. As mentioned earlier, for each disease we selected the major brain area known to exhibit early and serious neurodegeneration and compared it with the same area from age‐matched controls, as well as with another disease, where the analysed area is known to be spared from neurodegeneration (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next addressed the question whether HSPB8 and BAG3 expression may be upregulated in brain under neuropathological conditions characterized by the accumulation of misfolded aggregate‐prone proteins, including AD, PD, HD and SCA3 (Table S2). Under all these four pathological conditions, neurodegeneration is usually also accompanied by astrogliosis and microglia activation in the degenerating areas [2,42–45]. As mentioned earlier, for each disease we selected the major brain area known to exhibit early and serious neurodegeneration and compared it with the same area from age‐matched controls, as well as with another disease, where the analysed area is known to be spared from neurodegeneration (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…© 2011 The Authors Neuropathology and Applied Neurobiology © 2011 British Neuropathological Society, 38,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] …”
mentioning
confidence: 99%
“…The involvement of the corpus callosum is also a frequent finding in diffusion tensor imaging (DTI) studies and is proposed to be characteristic of Wallerian‐type degeneration; however, systematic neuropathological evaluations of the corpus callosum are lacking to support that view. Few autopsy reports have provided initial support for gliosis, but not a demyelinating pathology in the corpus callosum . Phosphorylated TDP‐43 inclusions, which are considered a hallmark pathological feature of ALS, are also reportedly absent in the corpus callosum .…”
Section: Discussionmentioning
confidence: 99%
“…In general, reduction of FA has been associated with neuronal loss with astrogliosis and myelin breakdown [Beaulieu et al, 1996]. In ALS, postmortem examinations have shown neuronal loss or atrophy and ubiquitin-positive intraneuronal inclusions extending beyond the motor system in patients with ALS with and without cognitive impairment [Mackenzie and Feldman, 2003;Murray et al, 2006;Tsuchiya et al, 2002]. Also, functional imaging studies have demonstrated hypometabolism in frontal and temporal cortices [Abrahams et al, 1996;Kew et al, 1993], which further provides support for ALS as being a multisystem disease.…”
Section: Fa and MD In Alsmentioning
confidence: 99%